Penerapan Ice Breaking Pada Pembelajaran Tematik di Sekolah Dasar - Lesi Oktiani Putri; Yona Wahyuningsih (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
The learning method by means of lectures is felt to be very boring for students in participating in the teaching and learning process. The purpose of this study was to analyze the application of ice breaking in thematic learning for elementary school students. The research method used is descriptive method with a qualitative approach. This type of research is field research. Data collection techniques used are observation, interviews, and documentation. The conclusion of the research shows that the ice breaking technique can be used in thematic learning in elementary schools. The implication of this research is that teachers can apply ice breaking techniques in learning activities, so that learning becomes fun.